Pharmacists’ Roles and Practices in Pharmaceutical Services During Covid-19 Pandemic: a Qualitative Study - Anna Wahyuni Widayanti; Shahiroh Haulaini; Susi Ari Kristina (Indonesian Journal of Pharmacy, 2022)
The World Health Organization (WHO) declared COVID-19 a global pandemic on March 11, 2020. Pharmacists as health workers also have an important role in this pandemic. This study wants to look deeper into how pharmacists perceive their role and pharmaceutical services during this pandemic. A qualitative study with Focus Group Discussions (FGDs) was utilized. Fifteen pharmacists from Kepulauan Riau province were involved. They were purposively selected to include pharmacists from the community pharmacies, hospitals, and community health centers. The FGDs were conducted with Zoom meetings and were recorded. The data were then transcribed and analyzed with inductive content analysis.  This study found five themes with 18 sub-themes. The five themes are the roles and efforts of pharmacists in managing medicines, medical devices, and disposable medical materials (personal protective equipment); the roles of pharmacists in providing pharmaceutical care; community behaviors during the pandemic; development of pharmacists’  roles and capacity during the pandemic; and external factors influencing the roles and practice of pharmacists during the pandemic. During the pandemic, pharmacists continued to work according to their previous roles and adjusted their roles and practice in pharmaceutical services to follow changes in community behaviors.  This condition also encouraged pharmacists to develop their roles and capacities. The healthcare management team, the government, and the professional organizations influenced their roles, both positively and negatively. The results of this study provide a deeper understanding of pharmacist roles and practices during the pandemic. This understanding will be useful for the pharmacist in developing their potential and capability to be involved as healthcare professionals, specifically during the pandemic situation and generally in disaster management.